2007
DOI: 10.1111/j.1469-8749.2005.tb01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Education and employment prospects in cerebral palsy

Abstract: Parents and paediatric neurologists need information on the long-term social prognosis of children with cerebral palsy (CP). No large population-based study has been performed on this topic. On 31 December 1999, to find predictors in childhood of subsequent education and employment, 819 participants with CP born between 1965 and 1978 (471 males; mean age 28y 10mo, SD 4y, range 21 to 35y) in the Danish Cerebral Palsy Registry were compared with 4406 controls without CP born between 1965 and 1978 (2546 males; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 21 publications
2
38
1
3
Order By: Relevance
“…Data from the Danish cerebral palsy register reported that 38% received schooling beyond lower secondary school. 31 There seems to be a tendency for more integration in the younger group of our study population, with 60% visiting mainstream high schools. This might reflect the implementation of legislation promoting inclusion, with increasing numbers of children with disabilities being fully integrated or put in self-contained classes (special education classes within the inclusive school).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Data from the Danish cerebral palsy register reported that 38% received schooling beyond lower secondary school. 31 There seems to be a tendency for more integration in the younger group of our study population, with 60% visiting mainstream high schools. This might reflect the implementation of legislation promoting inclusion, with increasing numbers of children with disabilities being fully integrated or put in self-contained classes (special education classes within the inclusive school).…”
Section: Discussionmentioning
confidence: 90%
“…27 Michelsen et al have recently reported similar findings in Denmark. 31 Slightly above a third of the respondents are currently working, 23% in competitive employment and 15% in sheltered work places. A few small studies have been published on employment among young adults with cerebral palsy.…”
Section: Discussionmentioning
confidence: 99%
“…42 Children with hemiplegia are more likely to function in mainstream school environments alongside their typically developing peers when compared with other CP types, 43 and improvements in self-worth are likely to influence their socialization, peer relations, and other areas of functioning. The use of BTX-A has been noted to enhance self-esteem by diminishing inappropriate motor responses 44 ; however, these were not evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy. Epilepsy can potentially severely limit the quality of life for the person with CP and their family, and adults with CP and epilepsy are less likely to find employment [Michelsen et al, 2005]. Epilepsy occurs in 30% of individuals with CP [Arnaud et al, 2008;ACPR Group, 2009].…”
Section: Quadriplegia (Tetraplegia)mentioning
confidence: 99%